Strengthening the quality of educator-child interactions in early childhood education and care settings: a conceptual model to improve mental health outcomes for preschoolers. Issue 7 (18th May 2020) - Blewitt, Claire; Morris, Heather; Nolan, Andrea; Jackson, Kylie; Barrett, Helen; Skouteris, Helen
ABSTRACT: High-quality early childhood education and care (ECEC) programmes can strengthen the social, emotional and cognitive skills that are crucial for future learning and wellbeing. Teacher–child interactions are the most vital component of ECEC service quality in terms of children's social-emotional functioning. However, many children are not consistently exposed to the quality of interactions required for optimal development. We propose a conceptual model to encourage social and emotional learning in preschoolers by targeting the quality and intentionality of teacher–child interactions. We draw upon two frameworks relevant in early childhood settings, the Teaching Through Interactions Framework, describing the type of interactions associated with positive child outcomes, and The Pyramid Model for Supporting Social Emotional Competence in Infants and Young Children, a tiered, systematic approach to implement strategies that improve social-emotional health. This model could inform the development of social and emotional learning programmes that support educators to apply responsive techniques through everyday interactions.